Identification of a novel interaction of FUS and syntaphilin may explain synaptic and mitochondrial abnormalities caused by ALS mutations - Shaakir Salam (Nature Portfolio, 2021)
Abstract Aberrantly expressed fused in sarcoma (FUS) is a hallmark of FUS-related amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Wildtype FUS localises to synapses and interacts with mitochondrial proteins while mutations have been shown to cause to pathological changes affecting mitochondria, synapses and the neuromuscular junction (NMJ). This indicates a crucial physiological role for FUS in regulating synaptic and mitochondrial function that is currently poorly understood. In this paper we provide evidence that mislocalised cytoplasmic FUS causes mitochondrial and synaptic changes and that FUS plays a vital role in maintaining neuronal health in vitro and in vivo. Overexpressing mutant FUS altered synaptic numbers and neuronal complexity in both primary neurons and zebrafish models. The degree to which FUS was mislocalised led to differences in the synaptic changes which was mirrored by changes in mitochondrial numbers and transport. Furthermore, we showed that FUS co-localises with the mitochondrial tethering protein Syntaphilin (SNPH), and that mutations in FUS affect this relationship. Finally, we demonstrated mutant FUS led to changes in global protein translation. This localisation between FUS and SNPH could explain the synaptic and mitochondrial defects observed leading to global protein translation defects. Importantly, our results support the ‘gain-of-function’ hypothesis for disease pathogenesis in FUS-related ALS.